Implementation of Al-Qur’an Memorization Learning to Improve Soul Cleansing from an Islamic Counseling Perspective in Islamic Junior High School in Deli Serdang District - Zulfahmi Hasibuan; Saiful Akhyar Lubis; Syaukani (Universitas PGRI Yogyakarta, 2026)
This study analyzes the implementation of Al-Qur'an memorization aas a means of cleansing the soul (tazkiyah an-nafs) from an Islamic counseling perspective in two Islamic junior high schools in Deli Serdang Regency: Al-Azhar Asy-Syarif Islamic Junior High School and Bintang Islamic Junior High School. Using a qualitative, phenomenological approach, the study involved the principal, the memorization teacher, the guidance counselor, the homeroom teacher, and the students as informants. Data were collected through in-depth interviews, observation, and documentation. The results of the study show: (1) The planning of the tahfidz program in both schools is oriented towards memorization as well as cleansing the students' souls in the context of Islamic counseling; (2) Implementation focuses on the integration of spiritual values ​​through the talaqqi method and independent learning; (3) Evaluation includes cognitive, affective, and spiritual aspects through monthly tasmi', tasmi' akbar, and jilsat itqon; (4) Obstacles include differences in students' cognitive abilities, heterogeneous educational backgrounds, and limited learning time; (5) The program's advantages are seen in the improvement of students' noble morals, discipline, and peace of mind. This research provides theoretical and practical contributions to the development of a holistic and meaningful tahfidz learning model within modern Islamic education. Keywords: tahfidz Al-qur'an, tazkiyah an-nafs, islamic counseling, character education